Using CRIU with HPC Containers Field Experience (International Journal of Engineering and Computer Science, 2018)
The paper provides an overview of current authors’ field experience of using CRIU for checkpoints and restores of computing containers with HPC applications. Docker and Singularity containers are considered. Reasonable results are obtained for locally running applications. Problems associated with providing the same features for distributed MPI applications are discussed, and possible solutions are outlined with the regard to current state of development of CRIU, Docker, Singularity, Open MPI and competing technologies.